The Effect of Wave Squad Training on the Smash Results of Volleyball Games for Extracurricular Students at SDN 2 Lembak - Juarsah, Edi; Handayani, Widya; Rizhardi, Rury (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to evaluate the impact of wave squad training on smash performance in volleyball games among extracurricular students at SDN 2 Lembak. The research method used is experimental with a pre-test and post-test control group design. The sample of this study consists of extracurricular volleyball students at SDN 2 Lembak, divided into two groups: the wave squad training group and the control group. The results of the study show that wave squad training has a positive effect on smash performance in volleyball games among extracurricular students. The implication of this study is the importance of incorporating wave squad training into volleyball training programs to enhance students’ smash abilities.